2012
DOI: 10.1037/a0029517
|View full text |Cite
|
Sign up to set email alerts
|

Interference between outcomes, spontaneous recovery, and context effects as measured by a cued response reaction time task: Evidence for associative retrieval models.

Abstract: The most common associative explanation of interference is based on a retrieval failure. Retrieval, in turn, is considered as the result of an associative activation mechanism that is thought to be fast and automatic. However, up-to-date, there is no evidence of interference based on dependent measures specifically related to this kind of low level processes. The objective of the present study was to test whether interference phenomena can be observed by using a cued response task designed to detect low level … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
19
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(21 citation statements)
references
References 39 publications
2
19
0
Order By: Relevance
“…One alternative approach for learning focuses on testing whether higher-order processes are critical to learning, by manipulating the availability of either time (González-Martín et al, 2012;Vadillo & Matute, 2010) or cognitive resources (De Houwer & Beckers, 2003;Waldmann & Walker, 2005). Though the introduction of such methodologies is refreshing, these specific findings yielded only ambiguous evidence for cognitively demanding processes in learning.…”
Section: Converging Measures Of Learningmentioning
confidence: 99%
See 1 more Smart Citation
“…One alternative approach for learning focuses on testing whether higher-order processes are critical to learning, by manipulating the availability of either time (González-Martín et al, 2012;Vadillo & Matute, 2010) or cognitive resources (De Houwer & Beckers, 2003;Waldmann & Walker, 2005). Though the introduction of such methodologies is refreshing, these specific findings yielded only ambiguous evidence for cognitively demanding processes in learning.…”
Section: Converging Measures Of Learningmentioning
confidence: 99%
“…Regardless, the very nature of the standard input-output paradigm clearly places an overwhelming emphasis on accurately predicting the transformation from covariation to judgment, with far less regard for the psychological mechanisms by which such a transformation comes about. More recently, researchers have started to investigate the trial-by-trial processing underlying learning, by employing nontraditional learning paradigms (De Houwer & Beckers, 2003;González-Martín, Cobos, Morís, & López, 2012;Le Pelley, Vadillo, & Luque, 2013;Vadillo & Matute, 2010;Waldmann & Walker, 2005), eyetracking Kruschke, Kappenman, & Hetrick, 2005;Le Pelley, Beesley, & Griffiths, 2011;Wills, Lavric, Croft, & Hodgson, 2007), and electroencephalography (Luque, López, Marco-Pallares, Càmara, & Rodríguez-Fornells, 2012;Morís, Luque, & Rodríquez-Fornells, 2013;Walsh & Anderson, 2011). These studies represent a refreshing alternative to the traditional input-output paradigm.…”
Section: The Need For Direct Evidencementioning
confidence: 99%
“…Thus, it may be questioned whether differences between target responses to A-1 and B-3 trials may be genuinely regarded as interference or whether the absence of differences between responses to these target trials may be regarded as recovery from interference effects. To avoid this problem, González-Martín et al (2012), in their Experiment 1, showed that training a series of consistent cue-outcome pairings in a first phase, just as the B-3 relationship in the present study, caused facilitation responses at test when the outcome was preceded by the cue. Facilitation was evidenced by showing faster RTs to target than to control test trials in which the outcome was preceded by an unrelated cue (either old or new).…”
Section: Resultsmentioning
confidence: 79%
“…To conclude, the study reported here shows once more that the cued response RT task developed by González-Martín et al (2012) can be successfully used to study interference in human predictive leaming and, specifically, the mechanism by which the context modulate retrieval in interference preparations. The renewal effects found in Experiments 1 and 2 are consistent with the idea that the context of the interfering training works as an and-gate that conditions the interfering associations formed during leaming rather than as an additional stimulus that form direct associations with the outcomes.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation